ANALISIS PERMINTAAN RUMAH SEDERHANA DI KOTA SEMARANG - Mulyo Budi S (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2009)
The government and private had unable to fullfill the demand of simly house inSemarang that compare with the increasing of population. This condition impact to thecitizens of Semarang City as the consumers, they can not buy a simply house.This reasearch focused on analysis factors that influence toward the demand of thesimply house in Semarang City. Analysis with multiple linear regression used in thisresearch.The result shows that simply house price, consumer income, credit interest rate, renthouse price and location distance were influenced toward the demand of simply house.Keywords: demand, elasticity, price, interest rate